Stunting prevention education for pregnant women and parents of toddlers in Barisan Village, Losari District - Maharani Susilowati; M. Haidar Ar Rasyid; Dhiyaa Anisah; Lailatul Salamah; Bella Putri Firanti; Mutiara Agustianti; Alfi Oktavia; Amanda Aulia Azahrah; Fatih Nandika Hakim; Fajar Willy Ahzami; Deni Firmansyah (Universitas Muhammadiyah Magelang, 2023)
According to the Ministry of Health of the Republic of Indonesia, stunting has the potential to slow down brain development, with long-term impacts, namely lower learning ability and the risk of obesity. Barisan Village has the highest rate due to lack of parental awareness, lack of sanitation and lack of knowledge about nutrition before and during pregnancy, and the decline in children's attendance at posyandu. The aim of the community service program is to provide education to parents of toddlers and pregnant mothers in Barisan Village about stunting and how to prevent it so that it can reduce the stunting rate. Activities are carried out through stunting education using the lecture method. The results of the program show that the residents of Barisan Village have increased insight and understanding regarding stunting and its prevention.